The political psychology of globalization Muslims in the west - Kinnvall, Catarina; Nesbitt-Larking, Paul W. (Paul Wingfield) 1954-; Oxford scholarship online (Online service). (New York Oxford University Press, 2011)
In an increasingly globalized world, there are new economic strategic, cultural, and political forces at work. This book explores how these shifts and shocks have influenced the way in which Muslim minorities in Western countries form their identities as political actors.
Includes bibliographical references and index.
Keywords: Globalization -- Social aspects; Globalization -- Psychological aspects; Muslims -- Western countries -- Politics and government; Muslims -- Western countries -- Social conditions; Muslims -- Ethnic identity; Muslims -- Cultural assimilation; Muslim diaspora; Multiculturalism; Electronic books; Western countries -- Emigration and immigration